2017
DOI: 10.1080/19440049.2017.1363417
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal modelling of the exposure of young UK patients with PKU to acesulfame K and sucralose

Abstract: Artificial sweeteners are used in protein substitutes intended for the dietary management of inborn errors of metabolism (phenylketonuria, PKU) to improve the variety of medical foods available to patients and ensure dietary adherence to the prescribed course of dietary management. These patients can be exposed to artificial sweeteners from the combination of free and prescribed foods. Young children have a higher risk of exceeding acceptable daily intakes (ADI) for additives than adults, due to higher food in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 27 publications
0
8
0
2
Order By: Relevance
“…A total of 19 European studies were identified from peer reviewed journals [51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69]. A further seven studies were identified from authoritative sources [70,71,72,73,74,75,76].…”
Section: Methodology and Trends In Intakementioning
confidence: 99%
See 4 more Smart Citations
“…A total of 19 European studies were identified from peer reviewed journals [51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69]. A further seven studies were identified from authoritative sources [70,71,72,73,74,75,76].…”
Section: Methodology and Trends In Intakementioning
confidence: 99%
“…Amongst the studies conducted using the Tier 2/Tier 3 approach [58,60,63,64,65,66,67,69], the assessments utilized the full range of consumption values from individuals in the sample population, combined with a single value for the MPL (Tier 2) or actual usage levels (Tier 3), considering a single value (simple distribution) [58,63,69], or the full range of use levels (probabilistic) [60,64,65,66,67]. …”
Section: Methodology and Trends In Intakementioning
confidence: 99%
See 3 more Smart Citations